Pengaruh Kepuasan Pernikahan dan Dukungan Sosial Suami terhadap Tingkat Stres Psikologis pada Ibu yang Bekerja - Nurhidayati Nurhidayati (Pelantar Press, 2026)
The purpose of this study was to determine the effect of marital satisfaction and husband's social support on stress levels in working mothers. This study is a quantitative study. Data were obtained through questionnaires distributed via Google Form. This study was conducted on January 5-16, 2026. The sample in this study were 52 working mothers. Data were analyzed using the SPSS data processing application. The results of descriptive analysis of 52 working mother respondents in this study showed that most were aged 30-35 years, totaling 22 people (42%), 36-40 years, totaling 16 people (31%), 41-45 years, totaling 10 people (19%) and 46-50 years, totaling 4 people (8%). The types of jobs in the respondents who participated in this study included, lecturers 15 people (29%), teachers 20 people (38%), employees 17 people (33%). The results of the study showed that there was a significant influence between Marital Satisfaction (X1) on Psychological Stress (Y1) with a significance value of 0.02 or 0.05. There was also a significant relationship between Husband's Social Support (X1) on Psychological Stress (Y1) with a significance value of 0.00 or 0.05. The results of the simultaneous test showed that there was an influence of marital satisfaction and husband's social support on the psychological stress of working mothers with a significance value of 0.00 or 0.05